Isolation, characterization and biomimetic oxidation of selected marine natural products and their analogues - Mutsvairo, Tafadzwa (Rhodes University, Faculty of Pharmacy, Pharmacy, 2016)
Marine brown algae produce a variety of terpenes with a wide range of biological activities. However, very few phytochemical studies of brown algae have been conducted in South Africa. Therefore, in our continued search for biologically active natural products, we examined the South African brown alga Brassicophycus brassicaeformis. The dichloromethane-methanol extract of B.brassicaeformis was fractionated by silica gel column chromatography followed by normal phase HPLC to give pure four pure compounds which were identified by spectroscopic methods as; fucosterol, fucoxanthin and two monogalactosyldiacylglycerol lipids. Many potential drug molecules such as natural products have failed to reach the market due to poor pharmacokinetic and metabolic profiles despite having potent biological activity. Therefore the importance of early drug metabolism studies in the drug development process is clear. A biomimetic oxidation model was used for in vitro drug metabolism studies to predict any possible metabolites that could be produced by these natural products. Two biomimetic oxidation models catalyzed by two water soluble metalloporphyrins as biomimics of cytochrome P450, in the presence of two terminal oxidants either hydrogen peroxide or iodobenzene diacetete were successfully developed. The models were applied to a range of natural products. The oxidation of the quinone natural products, sargahydroquinoic acid, and lapachol was most easily achieved by metalloporphyrins employed in this study.
Keywords: Uncatalogued